Design And Contruction of Waterbath Based Microcontroller - I Made Agus Mahardiananta; I Gusti Agung Haryawan; Putu Deva Prihananta; I Nyoman Satya Indra Guna (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
The existence of sophisticated equipment is always needed in the laboratory. Purpose is to support the laboratory and support the laboratory staff to work safely and comfortably. One tools commonly used in laboratory is waterbath. In this study, a microcontroller-based waterbath was designed which was equipped with time module for setting the heating time and buzzer as marker when the heating time was complete. In addition, this tool is also equipped with temperature settings from 400C - 950C. This research is an exploratory descriptive research The results of testing the waterbath tool show that the 5 minute time setting has an error percentage value of 3.5%, 10 minutes is 2.3%, 15 minutes is 0.05%, 20 minutes is 1.01%, 25 minutes is 0.001% and 30 minutes is 0.2%. Then the temperature test of 400C has a percentage error of 0.7%, 500C is 0.9%, 600C is 0.8%, 700C is 0.8%, 800C is 1.8%, 900C is 2.7% and 950C is 2.0%. In addition, this tool also meets the standard according to function with a size of 20x20x30cm which is ideal for operation.